2017
DOI: 10.2147/rrtm.s122046
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites in public transport buses from the city of Diamantina, Minas Gerais, Brazil

Abstract: BackgroundIntestinal parasites’ eggs, larvae, or cysts can be carried in public transport buses, and contribute to the increased incidence of diseases. This study aimed to detect biological forms of intestinal parasites in samples from public buses in the town of Diamantina, Minas Gerais, in order to know the local situation and propose interventions to improve public health.Materials and methodsIn November 2014, six samples were obtained in buses of the two stations by using Graham method, in duplicate, by af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Given the biological characteristics of Enterobius , the Graham method could potentially enhance positivity in studies. The Graham method has also been employed for environmental samples, such as public restroom surfaces and transportation means, where Enterobius presence has been reported in Brazil 10 , 57 - 59 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the biological characteristics of Enterobius , the Graham method could potentially enhance positivity in studies. The Graham method has also been employed for environmental samples, such as public restroom surfaces and transportation means, where Enterobius presence has been reported in Brazil 10 , 57 - 59 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of infective E. vermicularis eggs in public environments, such as bathrooms and buses, is concerning because of the possibility of contamination 10,[57][58][59] . This potential for contamination elucidates the sporadic instances of E. vermicularis infection.…”
Section: Prevalence Of Enterobius Vermicularis In Brazilmentioning
confidence: 99%
“…Previous studies conducted in the city of Diamantina have shown that the same intestinal parasites are also circulating in schools and buses. 16 , 17 It is noticed that the biological forms of these parasites are circulating in the most diverse environments and so it is necessary to establish public health policies and to encourage healthy habits. Thus, avoiding the transmission of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, significant advances have been made studying vulnerable rural-populations and how the displacement generated by the Colombian armed conflict has affected the life settings of these communities [ 3 6 ]. Populations with low quality of health, constant migration and displacement suffer serious parasitic diseases acting as temporal or permanent carriers, disseminating intestinal parasites [ 7 , 8 ]. Parasites such as helminths and protozoa are the most frequent, affecting more than 2 billion people worldwide, reaching a high prevalence in some regions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%